Low-temperature fired gray Yellow River sediment glass ceramic and preparation method thereof
The Yellow River silt and other raw materials were mixed by low-temperature firing to prepare gray Yellow River silt microcrystalline glass, which solved the problem of less research on Yellow River silt microcrystalline glass in the existing technology, and achieved high-value utilization of resources and reduced production costs.
Patent Information
- Application Number
- CN202411740500.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, there are few researches on the preparation of microcrystalline glass using Yellow River sediment, which has led to the fact that the high-value utilization and production cost control in this field have not been effectively solved.
The low-temperature firing method is adopted to prepare gray Yellow River silt microcrystal glass by mixing the Yellow River silt with other raw materials such as silica sand, CaCO3, Na2SiF6, Na2CO3 and B2O3-CuO-Bi2O3 oxides in a specific proportion, and through the steps of melting, forming, nucleating and crystallization.
It has achieved efficient low-temperature sintering of Yellow River silt, reduced the production cost of crystal-crystalline glass, provided new ways to utilize this resource at a high value, and improved the physical and chemical performance and application value of the product.
Smart Images

Figure CN119528438A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for low-temperature firing of grey Yellow River sediment microcrystalline glass using Yellow River sediment as a main raw material, belonging to the high-tech field of microcrystalline glass. Background Art
[0002] As a silicate resource, the Yellow River sediment has always been the focus of research on how to make high-value comprehensive utilization and turn waste into treasure. In the past decade, the Yellow River sediment has been widely used in building materials (sintered bricks, autoclaved bricks, ceramsite), industrial materials (molding sand, coated sand), flood control materials (artificial stone, slope protection bricks), agricultural materials (salt-alkali land improvement, greening planting soil), and artworks (clay inkstones, pottery).
[0003] At present, glass-ceramics mainly use industrial waste slag, industrial tailings, solid waste ash, etc. as raw materials. For example, the patent with application number CN201610294821.X discloses a cyanide tailings foamed glass-ceramics and its preparation method. Its main raw material is cyanide tailings (industrial waste slag), and foaming agent, nucleating agent, solvent and foam stabilizer are added to make glass-ceramics through preheating, foaming, crystallization and annealing. This invention uses cyanide tailings produced in gold smelting as the main raw material to prepare foamed glass-ceramics. However, there are few related studies on the use of Yellow River sediment to prepare glass-ceramics. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing gray glass-ceramics by low-temperature sintering of Yellow River sediment.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A low-temperature fired gray Yellow River sediment microcrystalline glass, the raw material composition is, by weight percentage: Yellow River sediment 50%-60%; silica sand 3%-10%; CaCO3 25%-30%; Na2SiF64%-8%; Na2CO3 5%-10%; in addition, B2O3-CuO-Bi2O3 oxide is added in an amount of 1%-4% by total weight of the above raw materials.
[0007] The pH value of the Yellow River sediment is 7.5-9, and the median particle size D 50 The diameter of the silica sand is 400nm, and the main chemical composition is: SiO2 54% to 68%, Al2O3 8% to 15%, CaO 5% to 10%, Fe2O3 2% to 6%, MgO 1% to 5%, K2O 1% to 5%, Na2O 1% to 5%, TiO2 0.1% to 3%. The median particle size D 50The diameter of the nanostructured carbon is 470 nm, and the main chemical composition is: SiO2 97% to 99%, Al2O3 0.01% to 3%, K2O 0.01% to 1%, CaO 0.01% to 1%, Fe2O3 0.01% to 1%, Cr2O3 0.01% to 1%, TiO2 0.01% to 1%, CuO 0.01% to 1%. The purity of CaCO3 is greater than 95%, D 50 450nm; Na2SiF6 purity is greater than 95%, D 50 350nm; Na2CO3 purity is greater than 95%, D 50 The molar ratio of B2O3, CuO and Bi2O3 in the oxide is 1:1:1; the purity of B2O3 is greater than 99%, and D 50 390nm; CuO purity is greater than 99%, D 50 440nm; Bi2O3 purity is greater than 99%, D 50 It is 410nm.
[0008] The low-temperature firing method of the gray Yellow River sediment glass-ceramics comprises the following steps:
[0009] (1) Melting: Place the Yellow River silt in an oven to dry, then mix it with other raw materials in a certain ratio and pour it into a lifting muffle furnace. Slowly heat it to 1300℃~1350℃ for sintering. Keep it at this temperature for 2h~3h to ensure that all the materials are melted; (2) Molding: Pour the molten glass into a mold at 400℃~600℃, cool it for 20s~30s, and obtain a glass plate; (3) Nucleation: Place the glass plate in a muffle furnace and heat it at 2℃ / min~5℃ / min. (4) Crystallization: Raise the temperature in the muffle furnace from 600°C to 700°C-740°C at a heating rate of 2°C / min-5°C / min to crystallize the glass plate for 3h-5h. Finally, cool the glass plate to room temperature in the furnace to obtain a semi-finished microcrystalline glass. (5) Post-processing: Cut and polish the semi-finished microcrystalline glass to obtain a finished product.
[0010] Beneficial effects of the present invention
[0011] (1) The present invention uses Yellow River silt as the main raw material. The Yellow River silt resources are abundant, cheap and easy to obtain. It not only solves the problem of the source of raw materials for preparing microcrystalline glass, but also provides a new way for the high-value utilization of Yellow River silt resources. At the same time, it can greatly reduce the production cost of microcrystalline glass, and has good economic value and social value.
[0012] (2) The present invention utilizes the properties of Yellow River silt as a silicate material. The raw material itself contains components such as SiO2, Al2O3, CaO, and Fe2O3, among which Fe2O3 can be used as a nucleating agent to cause nucleation inside the glass, which is beneficial to the preparation of microcrystalline glass with β-wollastonite as the main crystal phase.
[0013] (3) The raw material particles used in the present invention are relatively small, all of which are nanometer-level. Nanometer-level raw materials can increase the surface area of the particles, promote contact, diffusion and crystallization between particles, and help reduce the sintering temperature.
[0014] (4) Considering the high relative content of SiO2 in the Yellow River sediment and the high melting temperature of the raw materials, the present invention selects Na2CO3 and B2O3-CuO-Bi2O3 as fluxes. The chemical bonds of Na2CO3 break under high temperature conditions, and the generated alkaline oxides and CO2 reduce the melting temperature. 3+ , Cu 2+ 、Bi 3+ It enters the [Si(Al)O4] tetrahedrons to form a solid solution, causing lattice distortion, promoting grain boundary migration, and reducing the sintering activation energy, thereby achieving sintering at a lower temperature.
[0015] (5) The present invention reduces the sintering temperature of glass-ceramics from 1500°C to below 1350°C by controlling the particle size of the raw materials and the amount of flux added, thereby achieving low-temperature sintering of glass-ceramics and significantly reducing the preparation cost of glass-ceramics.
[0016] (6) The present invention selects Na2SiF6 as a nucleating agent and limits its addition amount. When the fluoride content in the system is greater than 4%, the fluoride is separated from the melt during the cooling process, which reduces the crystallization activation energy of the Yellow River sediment glass-ceramics and is beneficial to improving the physical and chemical properties of the glass-ceramics.
[0017] (7) The microcrystalline glass of the present invention has β-wollastonite as the main crystal phase. By adding silica sand with a high SiO2 content during the preparation process, the problem of insufficient SiO2 content in the basic glass component can be effectively solved.
[0018] (8) The gray microcrystalline glass of the present invention is a CaO-Al2O3-SiO2 system. The added CaCO3 decomposes into CaO under high temperature conditions, and CaO reacts with SiO2 to generate CaSiO3. Since CaO replaces SiO2, the network external volume will increase, the glass network connection strength will decrease, which is conducive to the movement of particles, thereby reducing the crystallization activation energy of the glass, increasing the number of crystals, and obtaining microcrystalline glass with a certain crystal size.
[0019] (9) The gray microcrystalline glass product of the present invention has good performance, with a bending strength greater than 115MPa and an impact toughness greater than 3.9kJ / m 2 , green and environmentally friendly, in line with the requirements of green building materials and JC / T 2097-2011 "Industrial Microcrystalline Glass Sheets", can be used in architectural decoration, machinery manufacturing, microelectronics technology, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD pattern of Yellow River sediment;
[0021] Figure 2 The gray Yellow River sediment glass-ceramics of Example 1;
[0022] Figure 3 SEM image of the gray Yellow River sediment glass-ceramics after HF etching treatment in Example 1;
[0023] Figure 4 XRD pattern of the gray Yellow River sediment glass-ceramics of Example 1;
[0024] Figure 5 FTIR image of the gray Yellow River sediment glass-ceramics of Example 1. DETAILED DESCRIPTION
[0025] The specific implementation methods of the present invention are further described in detail below in conjunction with the examples. Unless otherwise specified, the instruments and equipment involved in the examples are all conventional instruments and equipment; the raw materials involved are all commercially available conventional raw materials; and the test methods involved are all conventional methods.
[0026] Example 1 A low-temperature fired gray Yellow River silt glass-ceramic
[0027] The raw material composition by weight percentage is: Yellow River silt 51.1%, CaCO3 28.1%, silica sand 7.3%, Na2SiF6 6.2%, Na2CO3 7.3%, plus 2% B2O3-CuO-Bi2O3 oxide of the total weight of the above raw materials.
[0028] The main components of the Yellow River sediment are: SiO2 67.68%, Al2O3 12.43%, CaO 8.56%, Fe2O3 3.56%, K2O 2.46%, MgO 1.99%, Na2O 1.90%, TiO2 0.92%, pH 8.85, median particle size D 50 400nm; the main components of silica sand: SiO297.85%, Al2O31.50%, K2O 0.25%, CaO 0.17%, Fe2O30.12%, Cr2O30.04%, TiO20.04%, CuO 0.03%, median particle size D 50is 470nm; the purity of CaCO3, Na2SiF6, and Na2CO3 are all greater than 95%;
[0029] Preparation method of B2O3-CuO-Bi2O3 oxide: B2O3, CuO and Bi2O3 are respectively ball-milled twice by a high-energy ball mill at a speed of 2500 r / min for 3 min and 5 min, respectively, to obtain an oxide with a D50 of less than 500 nm. The median particle size D 50 They are 390nm, 440nm and 410nm respectively. The purity of the three components is greater than 99%, and the molar ratio of B2O3, CuO and Bi2O3 is 1:1:1.
[0030] The preparation method comprises the following steps:
[0031] (1) Melting: Place the Yellow River silt in an oven to dry, then mix it evenly with other raw materials in a certain proportion, pour it into a lifting muffle furnace, slowly heat it to 1350°C, and then keep it warm for 2 hours to ensure that all the materials are melted;
[0032] (2) Molding: Pour the molten glass into a mold at 600°C and cool for 30 seconds to obtain a glass plate. Immediately place the glass plate into a muffle furnace at 600°C to prepare for nucleation and crystallization.
[0033] (3) Nucleation: Place the glass plate in a muffle furnace and heat the temperature of the muffle furnace from 600°C to 740°C at a heating rate of 5°C / min for 2 h.
[0034] (4) Crystallization: The glass plate is crystallized by heating the muffle furnace to 850°C at a heating rate of 5°C / min for 3 hours, and then cooled to room temperature in the furnace to obtain a gray microcrystalline glass semi-finished product;
[0035] (5) Post-processing: Cut and polish the semi-finished glass-ceramics to obtain gray glass-ceramics products. The performance indicators of the obtained glass-ceramics products are shown in Table 1.
[0036] Table 1 Performance indicators of gray microcrystalline glass of Example 1
[0037] Performance Indicators result Bulk density <![CDATA[2.78g / cm 3 ]]> Water absorption 0.01% Wear <![CDATA[0.066g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.7% Alkali resistance (20% NaOH) 99.5% Impact toughness <![CDATA[4.53kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 130.39MPa Vickers hardness 732kgf / mm2 radioactivity <![CDATA[I Ra <0.1、I r =0.3]]>
[0038] The microscopic properties of the raw material Yellow River silt and the product of Example 1 were analyzed as follows:
[0039] Figure 1 The XRD diagram of the raw material Yellow River silt. It can be seen that the main component of the Yellow River silt is quartz, with a small amount of feldspar, microcline, magnetite and other substances.
[0040] Figure 2 This is a product photo of the gray Yellow River silt glass-ceramics of Example 1. It can be seen that the glass-ceramics is gray as a whole and feels silky, delicate and soft.
[0041] Figure 3 This is a SEM image of the gray glass-ceramics after HF etching treatment in Example 1. It can be seen that a large number of plate-like microcrystalline phases are generated in the glass-ceramics after HF etching treatment.
[0042] Figure 4 This is the XRD diagram of the gray Yellow River sediment glass-ceramics of Example 1. Analysis of the basic components of the glass-ceramics shows that the glass belongs to the ternary system of SiO2, Al2O3, and CaO, the main crystal phase is β-wollastonite (CaSiO3), and the grain size calculated by the Scherrer formula is 31.73nm.
[0043] Figure 5 This is the FTIR image of the gray Yellow River sediment glass-ceramics of Example 1. It can be seen that there are three infrared absorption bands in the FTIR spectrum, located at 850cm -1 ~1100cm -1 、600cm -1 ~800cm -1 and 400cm -1 ~500cm -1 . Among them, 400cm -1 ~500cm -1 The absorption band belongs to Si-O-Si bending vibration, 600cm -1 ~800cm -1 The absorption band at 850cm is caused by the stretching vibration of Si-O-Al and the symmetric stretching vibration of Si-O-Si. -1 ~1100cm -1 The absorption bands correspond to the antisymmetric stretching vibration of Si-O-Si and the vibration of Si-O.
[0044] Example 2 A low-temperature fired gray Yellow River silt glass-ceramic
[0045] The raw material composition is calculated by weight percentage: Yellow River silt 53.1%, CaCO3 28.1%, silica sand 7.3%, Na2SiF 64.2%, Na2CO3 7.3%, and B2O3-CuO-Bi2O3 oxide 2% of the total weight of the above raw materials. The performance requirements and preparation method of each raw material are the same as those in Example 1, and the performance indicators of the microcrystalline glass are shown in Table 2.
[0046] Table 2 Performance indexes of gray microcrystalline glass of Example 2
[0047] Performance Indicators result Bulk density <![CDATA[2.71g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.068g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.6% Alkali resistance (20% NaOH) 99.5% Impact toughness <![CDATA[4.38kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 126.38MPa Vickers hardness <![CDATA[725kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.3]]>
[0048] Example 3 A low temperature fired gray Yellow River silt glass-ceramic
[0049] The raw material composition is calculated by weight percentage: Yellow River silt 54.1%, CaCO3 26.6%, silica sand 7.3%, Na2SiF 66.2%, Na2CO3 5.8%, and B2O3-CuO-Bi2O3 oxide 2% of the total weight of the above raw materials. The performance requirements and preparation method of each raw material are the same as those in Example 1, and the performance indicators of the microcrystalline glass are shown in Table 3.
[0050] Table 3 Performance indexes of gray microcrystalline glass of Example 3
[0051] Performance Indicators result Bulk density <![CDATA[2.67g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.069g / cm 2 <!-- 4 -->]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.6% Alkali resistance (20% NaOH) 99.4% Impact toughness <![CDATA[4.15kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 122.20MPa Vickers hardness <![CDATA[718kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.3]]>
[0052] Example 4 A low temperature fired gray Yellow River silt glass-ceramic
[0053] The raw material composition is calculated by weight percentage: Yellow River silt 55.5%, CaCO3 25.3%, silica sand 6.5%, Na2SiF 65.5%, Na2CO3 7.2%, and B2O3-CuO-Bi2O3 oxide 3% of the total weight of the above raw materials. The performance requirements of each raw material are the same as those in Example 1.
[0054] Preparation method: The above raw materials are mixed evenly according to the proportion, poured into a lifting muffle furnace, sintered at 1350℃ and kept warm for 2h to ensure that all the materials are melted; the molten glass liquid is poured into a 600℃ mold, cooled for 30s to obtain a glass plate, and the glass plate is immediately placed in a 600℃ muffle furnace, and the temperature of the muffle furnace is increased from 600℃ to 720℃ at a heating rate of 5℃ / min for nucleation, and the nucleation time is 4h; then the temperature of the muffle furnace is increased to 880℃ at a heating rate of 5℃ / min for crystallization, and the crystallization time is 3h, and then cooled to room temperature with the furnace; the semi-finished microcrystalline glass is cut and polished to obtain a finished microcrystalline glass. The performance indicators of the obtained microcrystalline glass are shown in Table 4.
[0055] Table 4 Performance indexes of gray microcrystalline glass of Example 4
[0056] Performance Indicators result Bulk density <![CDATA[2.68g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.069g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.6% Alkali resistance (20% NaOH) 99.5% Impact toughness <![CDATA[4.25kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 123.15MPa Vickers hardness <![CDATA[720kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.3]]>
[0057] Example 5 A low temperature fired gray Yellow River silt glass-ceramic
[0058] The raw material composition is calculated by weight percentage: Yellow River silt 59.1%, CaCO3 25.1%, silica sand 3.3%, Na2SiF 65.2%, Na2CO3 7.3%, and B2O3-CuO-Bi2O3 oxide 2% of the total weight of the above raw materials. The performance requirements of each raw material are as in Example 1.
[0059] Preparation method: Mix the above raw materials evenly, pour them into a lifting muffle furnace, keep them at 1350℃ for 2h to ensure that all the materials are melted; pour the molten glass into a 600℃ mold, cool for 30s, then immediately put the glass plate into a 600℃ muffle furnace, heat the muffle furnace from 600℃ to 700℃ at a heating rate of 5℃ / min to nucleate the glass plate, and the nucleation time is 2h; then heat the muffle furnace to 900℃ at a heating rate of 5℃ / min to crystallize the glass plate, and the crystallization time is 3h, cool to room temperature with the furnace, cut and polish, and obtain the finished microcrystalline glass. The performance indicators of the obtained microcrystalline glass are shown in Table 5.
[0060] Table 5 Performance indexes of gray microcrystalline glass of Example 5
[0061] Performance Indicators result Bulk density <![CDATA[2.63g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.071g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.6% Alkali resistance (20% NaOH) 99.4% Impact toughness <![CDATA[3.95kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 117.31MPa Vickers hardness <![CDATA[711kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.3]]>
[0062] The SEM images, XRD images, and FTIR images of the glass-ceramics obtained in Examples 2 to 5 are basically the same as those in Example 1 and are not listed one by one.
Claims
1. A low-temperature fired gray Yellow River sediment glass-ceramics, characterized in that: Calculated by weight percentage, the raw material composition is: Yellow River silt 50% to 60%; silica sand 3% to 10%; CaCO3 25% to 30%; Na2SiF6 4% to 8%; Na2CO3 5% to 10%; in addition, 1% to 4% of the total weight of the above raw materials is added into B2O3-CuO-Bi2O3 oxide.
2. The low temperature fired gray Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The pH value of the Yellow River sediment is 7.5-9, and the median particle size D 50 It is 400nm, and its main chemical composition is: SiO2 54%~68%, Al2O3 8%~15%, CaO 5%~10%, Fe2O3 2%~6%, MgO 1%~5%, K2O 1%~5%, Na2O 1%~5%, TiO2 0.1%~3%.
3. The low temperature fired gray Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The median particle size D of the silica sand 50 It is 470nm, and its main chemical composition is: SiO2 97%~99%, Al2O3 0.01%~3%, K2O 0.01%~1%, CaO 0.01%~1%, Fe2O3 0.01%~1%, Cr2O3 0.01%~1%, TiO2 0.01%~1%, CuO 0.01%~1%.
4. The low temperature fired gray Yellow River silt glass-ceramics according to claim 1, characterized in that: The CaCO3 purity is greater than 95%, D 50 450nm; Na2SiF6 purity is greater than 95%, D 50 350nm; Na2CO3 purity is greater than 95%, D 50 It is 390nm.
5. The low temperature fired gray Yellow River silt glass-ceramics as claimed in claim 1, characterized in that: The molar ratio of B2O3, CuO and Bi2O3 in the oxide is 1:1:1; wherein the purity of B2O3 is greater than 99%, D 50 390nm; CuO purity is greater than 99%, D 50 440nm; Bi2O3 purity is greater than 99%, D 50 It is 410nm.
6. A low-temperature firing method for the gray Yellow River sediment glass-ceramics according to claim 1, characterized in that: The method comprises the following steps: (1) Melting: Put the Yellow River silt into an oven to dry, then mix it with other raw materials in a certain ratio and pour it into a lifting muffle furnace. Slowly heat it to 1300℃~1350℃ for sintering, and keep it at this temperature for 2h~3h to ensure that all the materials are melted; (2) Molding: Pour the molten glass into a mold at 400°C to 600°C and cool for 20s to 30s to obtain a glass plate; (3) Nucleation: Place the glass plate in a muffle furnace, raise the temperature of the muffle furnace from 600°C to 700°C to 740°C at a heating rate of 2°C / min to 5°C / min, and nucleate the glass plate for 2h to 4h; (4) Crystallization: raising the temperature in the muffle furnace to 850°C to 900°C at a heating rate of 2°C / min to 5°C / min to crystallize the glass plate for 3h to 5h, and finally cooling the glass plate to room temperature to obtain a semi-finished glass-ceramic product; (5) Post-processing: The semi-finished glass-ceramic products are cut and polished to obtain finished products.
Citation Information
Patent Citations
A kind of cyanidation tailing foam glass-ceramics and its preparation method
CN105819695B